The spatial distribution of sago palm landscape Sentani watershed in Jayapura District, Papua Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Dimara PA, Purwanto RH, Sunarta S, Wardhana W. 2021. The spatial distribution of sago palm landscape Sentani watershed in Jayapura District, Papua Province, Indonesia. Biodiversitas 22: 3811-3820. Sago palm is one of the starch sources used as local food in Papua, therefore this research aims to identify the supporting environment for the plant to grow by utilizing spatial data. The methods used were Spatial Analysis and Field Survey, where the first employed satellite imagery of Quickbird in 2012 and Landsat 8 in 2020 to distinguish between sago and non-sago palm landscape. In the process, five parameters were used, consisting of covering land elevation, slope gradient, soil type, rainfall as well as the optimal distance from the river and lake. The result showed the sago palm landscape in Sentani Watershed lies in the elevation of 0-450 m asl, while its largest habitat which lies between 0-100 m asl covering an area of 4,385.63 is found in a flat slope covering an area of 2,941.99 ha and in a very steep slope that spreads out over 41.92 ha. Generally, in Sentani Watershed, the plant grows in Mediterranean soil possessing thick solum with pH 5.0-7.0 and medium to great soil erodibility. Moreover, the largest habitat experiences a precipitation rate of 1,750 mm yr-1 covering a total of 6,846.24 ha, while the Doyo River has the largest sago palm landscape compared to other rivers.